Juridical Analysis of Human Trafficking in Batam City Viewing from Human Rights - Abdul Aziz; Alvien Septian Haerisma; Yuyun Yuningsih (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
This research was conducted in the coastal area of Gebang Mekar Village, Gebang District, Cirebon Regency. This study aims to analyze (1) the effect of working capital on the income of fishermen in Gebang Mekar, Cirebon Regency. (2) the effect of catches on the income of fishermen in Gebang Mekar, Cirebon Regency. (3) the effect of selling price on the income of fishermen in Gebang Mekar, Cirebon Regency. (4) the effect of working capital, catch, and selling price together on the income of fishermen in Gebang Mekar, Cirebon Regency. This study uses a quantitative descriptive approach with the type of survey research. The population in this study are fishermen who own the Gebang Mekar boat/ship. The sampling technique was purposive sampling with a total sample of 85 fishermen who own boats/ships. Data were collected through an open questionnaire. This study uses multiple linear regression analysis to determine the effect between the independent variables and the dependent variable. The results of this study found that: 1) working capital partially has no effect on the income of fishermen in Gebang Mekar, Cirebon Regency. 2) the catch has an effect on the income of fishermen in Gebang Mekar, Cirebon Regency. 3) the selling price has no effect on the income of fishermen in Gebang Mekar, Cirebon Regency. 4) working capital, catch, and selling price simultaneously affect the income of fishermen in Gebang Mekar, Cirebon Regency. Based on the results of this study, it was found that the catch variable was the most dominant variable contributing to fishermen's income obtained from fishing activities.